A Maine Policy Review Interview with Governor Angus S. King - Staff, Editorial (Maine Policy Review, 2006)
We had the pleasure of interviewing former governor Angus King about his views on Maine’s economy and future. In one hour we covered a lot of ground, touching on issues such as regionalization, the state’s role in economic development, and Governor King’s concerns about the nation.